OPTIMALISASI STRATEGI PENGELOMPOKKAN POTENSI PADI SEBAGAI SOLUSI EFEKTIF KELANGKAAN BERAS DI JAWA BARAT - Defi Yusti Faidah; Ashilla Maula Hudzaifa; Nadine Theresia; Carissa Egytia Widiantoro (LPPM Universitas Bina Bangsa, 2024)
Food security is a crucial issue for Indonesia, especially with the increasing threat of climate change. Focusing on rice production, this study analyses the mapping of districts/cities in West Java based on area harvested, rice production, and number of farm households using the Gaussian Mixture Model (GMM). GMM was chosen because it can overcome ambiguous data and has a large variance value. By using GMM, it is expected to find patterns or useful information from rice production data in West Java. Based on the results obtained, it can be seen that the best model is VEV with 5 clusters. Cluster 1 has characteristics of rice area, rice production, and number of farm households that are classified as low. The members of cluster 1 are Bogor, Sukabumi, Bandung, Ciamis, Kuningan, Sumedang, Purwakarta, West Bandung and Pangandaran. The results of this study are expected to help optimise rice production to meet food needs, reduce dependence on rice imports, and ultimately improve food security in Indonesia